Auswahl vermischter Schriften - Reinhold, Karl Leonhard (Karl Leonard Reinhold. Gesammelte Schriften, 2017)
This volume presents the amended version of Reinhold's award-winning script on the question of what progress metaphysics has made since Leibniz and Wolf in Germany (asked by the Preußische Akademie der Wissenschaften). The book includes the versions of the first main part, an introduction, and a detailed commentary.